Swimming anatomy. - McLeod, Ian, 1958- (Champaign : Human Kinetics, 2010)
See how to achieve stronger starts, more explosive turns, and faster times! Swimming Anatomy will show you how to improve your performance by increasing muscle strength and optimizing the efficiency of every stroke. Swimming Anatomy includes 74 of the most effective swimming exercises, each with step-by-step descriptions and full-color anatomical illustrations highlighting the primary muscles in action. Swimming Anatomy goes beyond exercises by placing you on the starting block, in the water, and into the throes of competition. Illustrations of the active muscles for starts, turns, and the four competitive strokes (freestyle, breaststroke, butterfly, and backstroke) show you how each exercise is fundamentally linked to swimming performance. You'll also learn how exercises can be modified to target specific areas, improve your form in the water, and minimize common swimming injuries. Best of all, you'll learn how to put it all together to develop a training program based on your individual needs and goals. Whether you are training for a 50-meter freestyle race or the open-water stage of a triathlon, Swimming Anatomy will ensure you enter the water prepared to achieve every performance goal.
Inhoudsopgave : Chapter 1. The Swimmer in Motion Chapter 2. Arms Chapter 3. Shoulders Chapter 4. Chest Chapter 5. Abdomen Chapter 6. Back Chapter 7. Legs Chapter 8. Whole-Body Training
Keywords: Sportfysiologie; Zwemmen